Perspectives of use of representatives of the genus complex Hemerocallis L. in antropogenic landscapes at Kryvorizhzhia (Ecological Bulletin of Kryvyi Rih District, 2019)
The deﬁnition of features of ﬂowering and variability of decorative characteristics of varieties of daylilies in the conditions of Kryvorizhzhya was carried out. The group of varieties, thatwas being grown in Kryvyi Rih botanical garden of NAS of Ukraine during 1999–2017, was investigated. The varieties were diﬀered on decorative signs and terms of ﬂowering. It was found that the early-middle varieties began to bloom in terms, which are characteristic for them, while the varieties of medium and mediumlate groups bloomed 12–15 days earlier. They recreated the development of the early-middle group. Flowering of varietal daylilies in our climatic conditions continues for 25–40 days. A signiﬁcant decrease in the diameter of the ﬂower, relatively to varietal characteristics at 5–41%, was recorded because of hot and dry conditions’ inﬂuence. While the height of a stem decreased to only 28%.  The varieties are attributed to the groups with the highest and middle level ofadaptation, that allows to use in anthropogenic landscapes with diﬀerent level of the technogenic loading.
Keywords: Hemerocallis L. cv.; the features of ﬂowerin; decorative characteristics; Kryvorizhzhya